2022
DOI: 10.22146/jtbb.71955
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification and Phylogenetic Tree Reconstruction of Marine Fish Species from the Fishing Port of Kutaradja, Banda Aceh

Abstract: The enormous potential of marine resources possessed by Banda Aceh Province is expected to be utilised optimally. Accuracy in marine fish resource identification is a critical requirement to support their utilisation and preservation in Banda Aceh Province. In this study, a molecular identification approach was carried out in addition to conducting a morphological identification, commonly used by several scientists. The results were 47 COI sequences generated representing 33 genera, 19 families, and five order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The molecular identification research that identified Variola albimarginata and Plectropomus leopardus from the western Indian Ocean was conducted in Simeulue and the North Coast of Aceh. In these studies, these two groupers were identified as highly abundant fish and displaying remarkably similar morphology, thereby necessitating meticulous morphological identification procedures to prevent mislabeling (Batubara et al 2017;Fadli et al 2021;Andriyono et al 2022). The genetic diversity of demersal fish was in a very high category at 0.98 (Table 5), where the range of genetic diversity was from 0 to 1 (Ramadhaniaty et al 2018).…”
Section: Commercially Important Demersal Fish In Nias Watersmentioning
confidence: 99%
“…The molecular identification research that identified Variola albimarginata and Plectropomus leopardus from the western Indian Ocean was conducted in Simeulue and the North Coast of Aceh. In these studies, these two groupers were identified as highly abundant fish and displaying remarkably similar morphology, thereby necessitating meticulous morphological identification procedures to prevent mislabeling (Batubara et al 2017;Fadli et al 2021;Andriyono et al 2022). The genetic diversity of demersal fish was in a very high category at 0.98 (Table 5), where the range of genetic diversity was from 0 to 1 (Ramadhaniaty et al 2018).…”
Section: Commercially Important Demersal Fish In Nias Watersmentioning
confidence: 99%